Peningkatan Literasi terhadap Lembaga Jasa Keuangan Bank pada Masyarakat Kelurahan Cawang Jakarta Timur - Riwandari Juniasti Purnama; Edison Siregar; Lis Sintha Oppusunggu; Fery Tobing (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2020)
Many people are familiar with banking institutions but not all are able to access banks and utilize banking products and understand the risks they face. Through Community Service activities in Cawang Village, East Jakarta, financial education is conducted to improve public financial literacy in Cawang Village, East Jakarta on financial services, financial services products, and how to get access to financial institutions especially banks, including providing knowledge on how to apply for credit to banks, as well as knowledge about the role of the Financial Services Authority (OJK) and the Deposit Insurance Corporation (LPS). The method used is financial education and to see the results of the impact on the material presented, an evaluation is carried out in the form of pre-test and post-test for participants present in the Kelurahan. The results of the PkM show that the literacy of PkM participants in Cawang Village in East Jakarta is quite good, because they already know OJK. LPS and banks and have transacted at banks. After financial education, 61.30% of participants experienced an increase in literacy. Literacy improvement is also determined by levels of education, age and gender. PkM participants can be said to have knowledge and confidence about financial service institutions and financial products and services, including features, benefits and risks, rights and obligations related to financial products and services Keywords: financial education; financial literacy; banking